Twentieth century socialism (Middlesex, 1956)
Socialist Union, the organization respon. sible for the views expressed in this book, was founded in 1951 by a group of Labour Party members. Their purpose was to think out afresh the meaning of socialism in the modern world. The Union's first publica tion, Socialism-a New Statement of Prin ciples, immediately received world-wide. publicity as a bold attempt at reformulating a socialist philosophy in terms appropriate to the mid-twentieth century. In Socialism and Foreign Policy which followed, the prin ciples were applied to international affairs. Now comes Twentieth Century Socialism, a challenging and controversial study of the nature of a socialist economic system, and the effect of economic organization on the life of man. One of the distinctive features of Socialist Union is that its publications present views which its members, broadly, hold in common. Drafts are of course writ ten by individuals, but they are first dis cussed in committees, then submitted for comment to meetings of all the members, and revised until a substantial measure of agreement has been found. The ideas of Socialist Union also find expression in the independent monthly journal Socialist Commentary.
Keywords: Socialism-20th century